2009
DOI: 10.1111/j.1365-2109.2009.02387.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding levels on growth performance, feed utilization, body composition and apparent digestibility coefficients of nutrients for juvenile Chinese sucker,Myxocyprinus asiaticus

Abstract: An experiment was conducted to determine e¡ects of feeding levels on growth performance, feed utilization, nutrient deposition, body composition and apparent digestibility coe⁄cients (ADCs) of nutrients for juvenile Chinese sucker (initial weight, 11.77 AE 0.22 g). Chinese sucker were fed a practical diet from 0% (starvation) to 4.0% (at 0.5% increments) body weight (bw) day À 1 for 8 weeks. The results showed that growth performance, feed utilization, nutrient deposition, body composition and ADCs of dry matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 75 publications
3
32
0
Order By: Relevance
“…They were gently siphoned from the fibreglass tanks into a 150‐mm screen, rinsed with distilled water, consistent with the methods used in the study (Yuan et al . ). Only freshly produced and intact faeces were collected to minimize nutrient and marker leaching.…”
Section: Methodsmentioning
confidence: 97%
“…They were gently siphoned from the fibreglass tanks into a 150‐mm screen, rinsed with distilled water, consistent with the methods used in the study (Yuan et al . ). Only freshly produced and intact faeces were collected to minimize nutrient and marker leaching.…”
Section: Methodsmentioning
confidence: 97%
“…Yuan et al . () reported that the optimum and maintenance feeding levels for Chinese sucker were 3.10% and 0.45% bw day −1 , respectively. However, limited studies, especially on the effects of replacement of fish meal with soybean meal (SBM), have been carried out for this fish.…”
Section: Introductionmentioning
confidence: 99%
“…; Yuan et al . ,, ) and no data are available on the dietary utilization of FSBM. The present experiment was undertaken to determine the potential of FSBM as partial substitutes for white fish meal (WFM) in the diet for Chinese sucker.…”
Section: Introductionmentioning
confidence: 99%